2022
DOI: 10.3390/su141912142
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Higher Education on Health Literacy: A Comparative Study between Urban and Rural China

Abstract: Health China 2030 calls for health equity. The strict household registration system, known as Hukou, results in an uneven distribution of social resources between urban and rural China. Higher education can promote social mobility and narrow health inequality. Health literacy is a significant indicator to predict health status. Drawing on national representative data recently collected, this study examines the impact of higher education on health literacy in urban and rural China. Propensity score matching was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…This finding contrasts with earlier studies, which typically indicate that higher education levels are associated with greater AD knowledge [ 30 , 32 , 45 ]. Although individuals with higher education might have better comprehension skills for understanding complex health issues, our data suggest that education level does not directly impact AD awareness [ 46 ]. Similarly, our research revealed no notable link between marital status and levels of AD knowledge, consistent with previous studies [ 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with earlier studies, which typically indicate that higher education levels are associated with greater AD knowledge [ 30 , 32 , 45 ]. Although individuals with higher education might have better comprehension skills for understanding complex health issues, our data suggest that education level does not directly impact AD awareness [ 46 ]. Similarly, our research revealed no notable link between marital status and levels of AD knowledge, consistent with previous studies [ 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we found disparities in FH, educational attainment, household income, healthcare coverage, and job type between urban and rural China, and education inequality can translate into health inequality. There is uneven distribution and utilization of public resources, with low health awareness and inadequate medical security in rural China ( 80 ). Second, in general, education may have a positive effect on FH both for urban and rural residents.…”
Section: Discussionmentioning
confidence: 99%
“…The primary explanatory variable was years of schooling (YS), with 0 denoting illiteracy, six denoting primary school, nine denoting junior high, 12 denoting high school, 15 denoting an associate's degree, 16 denoting a bachelor's degree, 19 denoting a master's degree, and 22 denoting a Ph.D. degree ( 80 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, future health education and health promotion activities should be reinforced too. (Long et al, 2022)…”
Section: Discussionmentioning
confidence: 99%